Can neighborhoods protect residents from mental distress during the COVID-19 pandemic? Evidence from Wuhan. Issue 1 (1st January 2021) - Miao, Jia; Zeng, Donglin; Shi, Zhilei
Abstract: Neighborhoods have begun to play an increasingly prominent role in shaping mental health during the coronavirus disease 2019 (COVID-19) pandemic because residents are spending more time at home and in their immediate neighborhoods. Using data collected from 3, 031 urban residents during the COVID-19 lockdown of Wuhan, China's earliest epicenter, this study investigates the relationship between neighborhoods' social infrastructure and residents' mental distress. Results of structural equation modeling estimation reveal that services provided by urban residents' committees ( cheng shi ju wei hui ) and volunteer groups significantly decrease the adverse impact of the COVID-19 outbreak on residents' mental health in a Chinese context, and social cohesion is one of the mechanisms underpinning this influence. Residents' committees and volunteer groups are found to increase their support when neighborhoods are facing an escalated level of COVID-19 risk. The residents who receive more support from their neighborhood organizations perceive a higher level of social cohesion and experience less mental distress. The findings suggest that mobilizing neighborhoods' organizational resources and fostering social cohesion are crucial strategies to minimizing residents' mental distress during COVID-19 pandemic.